"Spiritual Readiness" in the U.S. Military: A Neglected Component of Warrior Readiness - Koenig, Harold G. (Journal of religion and health, 2023)
Recent events have led to concerns about whether U.S. service members are "ready" to engage in combat operations. With most discussions now focused on military readiness, attention paid to warfighter readiness may have fallen behind. Service members typically receive extensive training in the tactical, physical, mental, social, and behavioral aspects of readiness, while the spiritual aspects are often ignored. This review examines (1) recent concerns over warfighter readiness, (2) mental health problems that are common among members of the U.S. military, (3) definitions and determinants of "spiritual readiness" (SR), (4) the impact of SR on human flourishing (HF) and warfighter readiness, (5) research on the effects of religious/spiritual involvement on HF, and (6) those responsible for building and sustaining SR in the military. An extensive body of research over the past 30 years has documented the impact of religious/spiritual (R/S) involvement on many aspects of human flourishing, thereby affecting the warfighter’s readiness to perform duties at the highest level. Military chaplains, mental health professionals, and medical providers all play important roles in building and sustaining the spiritual readiness of those in the U.S. military, thereby ensuring that these individuals perform in a way that maximizes their success during combat operations.